A retrospective, quantitative assessment of disease burden in patients with leptomeningeal metastases from non-small-cell lung cancer. Issue 5 (1st November 2019) - Nevel, Kathryn S; DiStefano, Natalie; Lin, Xuling; Skakodub, Anna; Ogilvie, Shahiba Q; Reiner, Anne S; Pentsova, Elena; Boire, Adrienne
Abstract: Background: Improvements in detection and molecular characterization of leptomeningeal metastasis from lung cancer (LC-LM) coupled with cerebrospinal fluid (CSF)-penetrating targeted therapies have altered disease management. A barrier to formal study of these therapies in LM is quantification of disease burden. Also, outcomes of patients with targetable mutations in LC-LM are not well defined. This study employs molecular and radiographic measures of LM disease burden and correlates these with outcome. Methods: We reviewed charts of 171 patients with LC-LM treated at Memorial Sloan Kettering. A subset had MRI and CSF studies available. Radiographic involvement ( n = 76) was scored by number of gadolinium-enhancing sites in 8 locations. CSF studies included cytopathology, circulating tumor cell (CTC) quantification ( n = 16), and cell-free DNA (cfDNA) analysis ( n = 21). Clinical outcomes were compared with Kaplan–Meier log-rank test and Cox proportional hazards methodologies. Results: Median overall survival was 4.2 months (95% CI: 3.6–4.9); 84 patients (49%) harbored targetable mutations. Among bevacizumab-naïve patients with MRI and CSF cytology at time of LC-LM diagnosis, extent of radiographic involvement correlated with risk of death (hazard ratio [HR]: 1.16; 95% CI: 1.02–1.33; P = 0.03), as did CSF CTC (HR: 3.39, 95% CI: 1.01–11.37; P = 0.048) and CSF cfDNA concentration (HR: 2.58; 95% CI: 0.94–7.05; P = 0.06). Those without a targetable mutation were almost 50% more likely to die (HR: 1.49; 95% CI: 1.06–2.11; P = 0.02). Conclusions: Extent of radiographic involvement and quantification of CSF CTC and cfDNA show promise as prognostic indicators. These findings support molecular characterization and staging for clinical management, prognostication, and clinical trial stratification of LC-LM.